A classification of genes involved in normal and delayed male puberty - Maleeha Akram; Syed Shakeel Raza Rizvi; Mazhar Qayyum; David J Handelsman (Asian Journal of Andrology, 2023)
Puberty is a pivotal biological process that completes sexual maturation to achieve full reproductive capability. It is a major transformational period of life, whose timing is strongly affected by genetic makeup of the individual, along with various internal and external factors. Although the exact mechanism for initiation of the cascade of molecular events that culminate in puberty is not yet known, the process of pubertal onset involves interaction of numerous complex signaling pathways of hypothalamo-pituitary-testicular (HPT) axis. We developed a classification of the mechanisms involved in male puberty that allowed placing many genes into physiological context. These include (i) hypothalamic development during embryogenesis, (ii) synaptogenesis where gonadotropin releasing hormone (GnRH) neurons form neuronal connections with suprahypothalamic neurons, (iii) maintenance of neuron homeostasis, (iv) regulation of synthesis and secretion of GnRH, (v) appropriate receptors/proteins on neurons governing GnRH production and release, (vi) signaling molecules activated by the receptors, (vii) the synthesis and release of GnRH, (viii) the production and release of gonadotropins, (ix) testicular development, (x) synthesis and release of steroid hormones from testes, and (xi)the action of steroid hormones in downstream effector tissues. Defects in components of this system during embryonic development, childhood/adolescence, or adulthood may disrupt/nullify puberty, leading to long-term male infertility and/or hypogonadism. This review provides a list of 598 genes involved in the development of HPT axis and classified according to this schema. Furthermore, this review identifies a subset of 75 genes for which genetic mutations are reported to delay or disrupt male puberty.